Deciphering the unusual fluorescence in weakly coupled bis-nitro-pyrrolo[3,2-b]pyrroles - Yevgen M. Poronik (Nature Portfolio, 2020)
Owing to their electron-withdrawing nature, nitro-groups are desirable in the design of electron-deficient light-sensitizing aromatic π-conjugated molecules, but most nitro-aromatics are not fluorescent. Here, the authors show how balanced donor-acceptor coupling ensures fast radiative deactivation and slow intersystem crossing in bis-nitrotetraphenylpyrrolopyrroles.